Home-made explosive found inside injured Afghan. Issue 2 (26th June 2014) - Pengelly, Steven; Moore, N; Burgess, D; Mahlon, M; Rowlands, T; Cubison, T
Abstract : There is extensive literature on metal fragments from improvised explosive devices being embedded in patients but there are no reports describing the clinical and radiological appearances of embedded home-made explosive (HME). We present a case of partially detonated HME being found inside a patient's forearm. We discuss the medical management of the injury, the ongoing risk to the patient and surgical team associated with the explosive and the safe disposal of the substance.